KONSEP NASIKH MANSUKH DALAM SERTIFIKASI HALAL - Muhammad Affandi AR; Halimah Basri, Nasrullah Bin Sapa (CV. Adiba Aisha Amira, 2024)
This study aims to analyze the concept of nasikh mansukh and its implications in Islamic law, particularly in the context of halal certification. Using a descriptive qualitative method, the study identifies differing opinions among scholars regarding the definition of nasakh. Some scholars define it as the annulment of the application of previous law, the prevention of the continuation of earlier law, or the expiration of the validity of the initial command. Despite the differing definitions, the impact remains the same: the annulled law is no longer applicable. In the context of halal certification, the concept of nasikh mansukh demonstrates the flexibility of Islamic law, allowing for the adjustment of rules to maintain public benefit, both in terms of fulfilling Sharia principles and addressing modern societal needs. This concept reflects how Islamic law is gradually prescribed to ensure its relevance, public welfare, and societal tranquility are consistently preserved.